Novel Parvoviruses from Wild and Domestic Animals in Brazil Provide New Insights into Parvovirus Distribution and Diversity - Souza, William Marciel de; Dennis, Tristan; Fumagalli, Marcilio Jorge; Araujo, Jansen; Sabino-Santos, Gilberto; Motta Maia, Felipe Goncalves; Acrani, Gustavo Olszanski; Torres Carrasco, Adriano de Oliveira; Romeiro, Marilia Farignoli; Modha, Sejal; Vieira, Luiz Carlos; Ometto, Tatiana; et al. (Mdpi, 2018)
Parvoviruses (family Parvoviridae) are small, single-stranded DNA viruses. Many parvoviral pathogens of medical, veterinary and ecological importance have been identified. In this study, we used high-throughput sequencing (HTS) to investigate the diversity of parvoviruses infecting wild and domestic animals in Brazil. We identified 21 parvovirus sequences (including twelve nearly complete genomes and nine partial genomes) in samples derived from rodents, bats, opossums, birds and cattle in Pernambuco, Sdo Paulo, Paran6 and Rio Grande do Sul states. These sequences were investigated using phylogenetic and distance-based approaches and were thereby classified into eight parvovirus species (six of which have not been described previously), representing six distinct genera in the subfamily Parvovirinae. Our findings extend the known biogeographic range of previously characterized parvovirus species and the known host range of three parvovirus genera (Dependovirus, Aveparvovirus and Tetraparvovirus). Moreover, our investigation provides a window into the ecological dynamics of parvovirus infections in vertebrates, revealing that many parvovirus genera contain well-defined sub-lineages that circulate widely throughout the world within particular taxonomic groups of hosts.
Keywords: parvovirus; Parvoviridae; ssDNA viruses; zoonotic viruses